2021
DOI: 10.1021/acs.jpcb.0c09285
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulations of Hydrophobic Gating of Pentameric Ligand Gated Ion Channels: Insights into Water and Ions

Abstract: Ion channels are proteins which form gated nanopores in biological membranes. Many channels exhibit hydrophobic gating, whereby functional closure of a pore occurs by local dewetting. The pentameric ligand gated ion channels (pLGICs) provide a biologically important example of hydrophobic gating. Molecular simulation studies comparing additive vs polarizable models indicate predictions of hydrophobic gating are robust to the model employed. However, polarizable models suggest favorable interactions of hydropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 126 publications
1
47
0
Order By: Relevance
“…extensively in the family of pentameric ligand-gated ion channels (pLGIC) 44 , which in general have symmetric or pseudo-symmetric structures in the ligand-free form. Intriguingly, the existence of asymmetric conformations has been observed in the absence of ligand for the serotonine receptor 5HT3R, revealing conformational plasticity also in the resting state.…”
Section: Relating To Other Classes Of Proteins and Channels Gating Has Been Investigatedmentioning
confidence: 99%
“…extensively in the family of pentameric ligand-gated ion channels (pLGIC) 44 , which in general have symmetric or pseudo-symmetric structures in the ligand-free form. Intriguingly, the existence of asymmetric conformations has been observed in the absence of ligand for the serotonine receptor 5HT3R, revealing conformational plasticity also in the resting state.…”
Section: Relating To Other Classes Of Proteins and Channels Gating Has Been Investigatedmentioning
confidence: 99%
“…Although PMFs for ions in a number of channels were obtained from MD simulations, in most cases no estimates of errors were provided [21,23,26,[53][54][55][56][57][58][59][60][61]. In a few cases in which errors are available by way of either direct estimates or comparisons of PMF obtained via different methods [20,24,25,[62][63][64][65][66][67][68] they are of the order of 0.2-0.7 kcal/mol, which is similar to what is expected to be the intrinsic accuracy of the formalisms studied here. This means that if there were differences between electrophysiological properties obtained from MD simulations at several applied voltages and reconstructed from simulations at a single voltage it would not be possible to determine whether these differences were due to insufficient accuracy of the simulations or to inaccurate reconstruction from the new methods.…”
Section: Introductionmentioning
confidence: 73%
“…Overall, the average number of water molecules in the bottleneck increased slightly when the electric field was present (Fig. 10a), a phenomenon seen in hydrophobic gates and known as "electric field-induced wetting" [35]. The overall degree of hydration in run #1 was greater than that of all other simulations conducted with an electric field.…”
Section: Hydration Of the Bottleneck Regionmentioning
confidence: 96%
“…10a, j-l). Electric-field-induced permeation of water and ions was observed in simulations of hydrophobic nanopores [65]; more recently, wetting of hydrophobic gates was demonstrated in simulations of biological ion channels in the presence of a strong electric field [35,66,67]. It has been suggested that the presence of an electric field can alter the liquid-vapour equilibrium of water inside hydrophobic gate, resulting in an increased probability of wetting [66].…”
Section: A Hydrophobic Gate With Unusual Featuresmentioning
confidence: 99%